The Rising Impact of HPV Infection in the Antiretroviral Therapy (ART) Era - Asensi-Díaz, Elia; Carrillo, Irene; Al-Hayani, Aws; Mejías-Ledesma, María; Guadalajara, Héctor; Azinovic, Ignacio; Domínguez Trsitancho, José Luis; Vidal, Llanos Salar; Castellano, Víctor; García-Olmo, Damián; Górgolas, Miguel; Cabello-Úbeda, Alfonso (Current HIV Research, 2025)
<span class=
Keywords: AIDS